Interface model for fracture behaviour of Fiber-Reinforced Cementitious Composites (FRCCs): theoretical formulation and applications - Caggiano, Antonio (2011)
This paper presents a model for fiber-reinforced cementitious composites (FRCCs) based on a cohesive-frictional interface theory. A zero-thickness joint model is formulated for simulating the fracture behaviour of interfaces between the various phases of fiber-reinforced concretes. In particular, the “Mixture Theory” is used for describing the coupled action between concrete and fibers. Numerical analyses have been carried out on both plain concrete and FRCC members. Comparisons between numerical simulation and experimental evidence demonstrate the accuracy and soundness of the proposed formulation.